Mapeamento, diagnóstico e nível de maturidade do processo de manutenção praticado por uma empresa do ramo de supermercados - Nosvitz, Alessandra Jaime (2023)
The first records of food trade occurred in a distant period, in the form of barter. Over the years, mass production encouraged the development of small establishments that later gave rise to modern supermarkets. The supermarket sector currently has a large representation in the national gross domestic product and, although it is classified as a commercial activity, it encompasses particularities that make the maintenance sector a fundamental pillar for its success. The maintenance process in these companies is usually responsible for the availability of all assets, its performance directly influences the quality of the products offered as well as the guarantee of food safety. Nonetheless, in the scientific literature, were located few researchers who approach the theme applief to this business segment. With that in mind, this document presents the results obtained from the case study carried out in a supermaket chain founded in 1924 and currently structured with several retail stores, a wholesale and a distribution center, alming to analyze the process of maintenance that was practiced. Initially, through on-site observations, basic information was collected and then mapped through the application of the Business Process Model and Notation (BPMN) method. Finally, the maturity level of the current process was diagnosed with support in ten classes that cover elements considered in the scientific literature fundamental to achieve excellence in maintenance. As a result, a process based mainly on informal techniques was verified, which presented a small level of maturity and many possibilities for improvement. Among the difficulties perceived, it is possible to highlight a high percentage of interventions of the corrective type, lack of control with the stock of spare parts and deficiency in te prioritization of activities. In addition, few processes were standardized, it wasn’t usual to keep a history of interventions or technical documents for the assets and, no support tools or performance measutement indicators were defined. However, the maintenance sector was seen by the current management as an ally in the company’s expansion strategy, therefore, the need for continuous development and improvement in the tasks performed was understood. With this analysis, it is intended to enable understanding of the general panorama of the company’s maintenance sector and to help define criteria to achieve better levels of maturation.